PELATIHAN PENGEMBANGAN INTERPRETASI WARISAN BUDAYA, VIRTUAL REALITY, DAN BAHASA INGGRIS PARIWISATA WARISAN DUNIA DARAJAT PAS BERBASIS WEB DENGAN AI-CHATBOTS UNTUK PARIWISATA - Agie Nugraha Pratama; Mersiana Setiarini; Nurul Rochmah Pramadika; Handa Gustiawan; Hesti Rian (JURNAL ABDIMAS PLJ, 2025)
The Training on the Development of Cultural Heritage Interpretation, Virtual Reality, and English in World Heritage Tourism Darajat Pass Web-based with AI-Chatbots for Tourism is a strategic effort to increase the capacity of local human resources and the competitiveness of the tourism sector in Karyamekar Village, Pasirwangi District, Garut Regency, West Java. Darajat Pass, located in Garut Regency, West Java, is a tourist destination with great natural and cultural potential, but still faces some fundamental challenges in its development. This training activity aims to equip MSME actors and farmer groups through an integrated training program that focuses on increasing the capacity of human resources through three main aspects: cultural heritage interpretation, tourism English proficiency, and the use of web-based technology, Virtual Reality (VR), and AI-chatbots. The training methods used include blended learning and participatory and question and answer and discussion. This training not only increases the confidence of participants, but also strengthens the readiness of Darajat Pass as a more competitive and friendly tourist destination for foreign tourists. It is hoped that this program will not only answer the three main needs of modern tourism—namely cultural interpretation, language mastery, and digitalization—but also have the potential to strengthen the competitiveness of the Darajat Pass as a technology-based cultural heritage tourism destination.